2023
DOI: 10.3390/cells12060918
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms in Autoimmune Thyroid Disease

Abstract: The most common cause of acquired thyroid dysfunction is autoimmune thyroid disease, which is an organ-specific autoimmune disease with two presentation phenotypes: hyperthyroidism (Graves-Basedow disease) and hypothyroidism (Hashimoto’s thyroiditis). Hashimoto’s thyroiditis is distinguished by the presence of autoantibodies against thyroid peroxidase and thyroglobulin. Meanwhile, autoantibodies against the TSH receptor have been found in Graves-Basedow disease. Numerous susceptibility genes, as well as epigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 324 publications
(239 reference statements)
0
56
0
1
Order By: Relevance
“…There is a strong genetic influence and heritability in the development of autoimmune dysthyroidism ( Shukla et al., 2018 ). It has been described as the activation of lymphocytes by lymphotropic viruses ( Vargas-Uricoechea, 2023 ). One hypothesis is that some viruses could interact with susceptibility genes in the immune regulatory systems (HLA-DR, CTLA-4, CD40, and PTPN22) and thyroid-specific genes (Thyroglobulin, TSHR) and trigger dysthyroidism through epigenetic modifications ( Tomer and Davies, 1993 ; Jacobson and Tomer, 2007 ; Hasham and Tomer, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a strong genetic influence and heritability in the development of autoimmune dysthyroidism ( Shukla et al., 2018 ). It has been described as the activation of lymphocytes by lymphotropic viruses ( Vargas-Uricoechea, 2023 ). One hypothesis is that some viruses could interact with susceptibility genes in the immune regulatory systems (HLA-DR, CTLA-4, CD40, and PTPN22) and thyroid-specific genes (Thyroglobulin, TSHR) and trigger dysthyroidism through epigenetic modifications ( Tomer and Davies, 1993 ; Jacobson and Tomer, 2007 ; Hasham and Tomer, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another hypothetical mechanism for dysthyroidism caused by the hepatitis C virus would be molecular mimicry where shared partial sequences of amino acid segments with the antigens of the thyroid tissue lead affect thyroid function ( Cuan-Baltazar and Soto-Vega, 2020 ). Certain HCV viral envelope proteins can be recognized at the thyroid level, such as the E2 glycoprotein, which can bind to CD81 receptors expressed on thyroid cells and thus induce a cascade of signaling pathways leading to the release of IL-8, a highly proinflammatory cytokine ( Akeno et al., 2008 ; Vargas-Uricoechea, 2023 ). A recent study in 2020 found that HCV infection of thyrocytes resulted in the production of the chemokine CXCL-8 and the pro-inflammatory cytokines tumor necrosis factor alpha (TNF-α) and a decrease in the expression of the thyroid peroxidase and thyroglobulin genes and an increase in the expression of the deiodinase 2 gene ( Hammerstad et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune thyroid diseases (AITD) are the most common form of organ-specific autoimmune diseases with an estimated prevalence of 5%, including a vast spectrum of manifestations ranging from hyperthyroidism, known as Graves' disease, to hypothyroidism, known as Hashimoto's thyroiditis, as well as cases with no history of clinical and biochemical findings (33,34). The pathophysiology of AITDs has been described as dysfunction of the normally established tolerance towards thyroid tissue antigens, infiltration of lymphocytes, subsequent activation of the inflammatory response, and production of the characteristic autoantibodies.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the disruption of immune tolerance is genetically driven [29]. Particularly, HT autoimmune anomalies are genetically based on gender and pre-existing susceptibility individual [28,30,31]. In turns, environment plays a critical role on altered genetic background by doing influence the disease development.…”
Section: Ht Biomarkers and Epidemiological Datamentioning
confidence: 99%
“…In turns, environment plays a critical role on altered genetic background by doing influence the disease development. [27,31]. Hence, HT is reported in women 10-15 times more often than men by an incidence peak around 30-50 years [32].…”
Section: Ht Biomarkers and Epidemiological Datamentioning
confidence: 99%